Geometry Design of Railway Track for High-Speed Railways Bandung-Cirebon KM 00+000 - KM 33+850 - Adya Aghastya; Aldi Wardana; Wahyu Tamtomo Adi; Nanda Ahda Imron; Willy Artha Wirawan (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Efficiency, comfort, speed and timeliness are the main factors humans need in mobilisation and transportation. In providing a theoretical basis and technical reference for the quality improvement of high-speed railways in Indonesia, this study comprehensively discusses the theory of geometrical design of high-speed railway tracks and the calculation of excavation and embankment volumes. By using Minister of Transportation regulations Number 7 of 2022 and TB 10621-2014, which contains technical planning for high-speed railway tracks, an alternative route is planned across Bandung to Cirebon Phase I (Rancaekek-Cimalaka) with an operating speed of 350 km/hour, there are 5 horizontal curves and 16 vertical curves calculated using TB 10621-2014 and AutoCAD Civil 3D software. The results obtained from this study are alternative planning of the high-speed railway route along 33,850 meters from Bandung to Cirebon Phase I (Rancaekek- Cimalaka).